2019
DOI: 10.1080/10580530.2019.1652448
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Social Networks as Digital Infrastructures - Understanding the Utilitarian Value of Social Media at the Workplace

Abstract: In this study, we first show that while both the perceived usefulness and perceived enjoyment of enterprise social networks impact employees' intentions for continuous participation, the utilitarian value significantly outpaces its hedonic value. Second, we prove that the network's utilitarian value is constituted by its digital infrastructure characteristics: versatility, adaptability, interconnectedness and invisibility-in-use. The study is set within a software engineering company and bases on quantitative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 97 publications
(160 reference statements)
1
19
0
1
Order By: Relevance
“…New health discoveries and techniques are frequently shared through instant messaging apps which have increased the knowledge of health professionals. The implementation of socialization-oriented social media in public organizations is a complex task because social media is commonly used by individuals and is complex to manage as an organizational platform to improve employee performance (Meske et al, 2019). On the other hand, social media is a major source of knowledge sharing, information exchange and collaborative networking, and it can improve employee performance (Hammond and Wellington, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…New health discoveries and techniques are frequently shared through instant messaging apps which have increased the knowledge of health professionals. The implementation of socialization-oriented social media in public organizations is a complex task because social media is commonly used by individuals and is complex to manage as an organizational platform to improve employee performance (Meske et al, 2019). On the other hand, social media is a major source of knowledge sharing, information exchange and collaborative networking, and it can improve employee performance (Hammond and Wellington, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Early in the development of ESM, Schneckenberg (2009) argued that perceived ease of use contributes to the massive use of ESM. For the perceived usefulness of ESM, perceived usefulness of ESM impact employees' intentions for continuous (Meske et al, 2019), and employees with an objective perception will engage in the use of the ESM, while employees with a skeptical perception will hinder their use (Treem et al, 2015;Vuori and Okkonen, 2012). In addition, from the social exchange perspective, Paroutis and AI Saleh (2009) suggested that employees who perceive positive outcomes from using ESM are more likely to actively participate, while those who are unaware of the benefits are the ones refraining from using ESM.…”
Section: Analysis Of Landmark Research In the Esm Literaturementioning
confidence: 99%
“…Hence utilitarian motivation helps encourage employees to polish their skills and abilities to increase their task performance (Chun et al, 2012). Studies also support that utilitarian motivation is focused on the achievement of useful outcomes, and hence is a strong predictor of individual work-related behavior (Kim & Hall, 2019;Meske et al, 2019). Employees that are motivated based on this aspect desire financial rewards that help them increase their productivity and the efforts directed towards increasing pay per performance (Wu & Ma, 2015).…”
Section: Utilitarian Motivation -Knowledge Sharing Through Ess Use -Employee Productivitymentioning
confidence: 99%
“…This allows companies to increase productivity by saving costs and time related to traditional R&D by taking advantage of the information shared by employees (Kwahk & Park, 2016a). Systems that are technology-based and reward employees for their knowledge sharing in terms of monetary incentives, promotions, and leisure trips are better in improving the knowledge sharing behavior of employees (Meske et al, 2019). As these technology-based systems target the utilitarian motivation of their employees by rewarding their knowledge-sharing behavior they are better able to promote competition among employees and hence increase productivity (Nyanga & Zirima, 2020).…”
Section: Utilitarian Motivation -Knowledge Sharing Through Ess Use -Employee Productivitymentioning
confidence: 99%